Case Report: A Synonymous Mutation in NF1 Located at the Non-canonical Splicing Site Leading to Exon 45 Skipping - Jin, Pengzhen; Yan, Kai; Ye, Shaofen; Qian, Yeqing; Wu, Zaigui; Wang, Miaomiao; Xu, Yuqing; Xu, Yanfei; Dong, Minyue (Frontiers in Genetics, 2021)
Synonymous mutations are generally considered non-pathogenic because it does not alter the amino acids of the encoded protein. Publications of the associations between synonymous mutations and abnormal splicing have increased recently, however, not much observations available described the synonymous mutations at the non-canonical splicing sites leading to abnormal splicing. In this pedigree, the proband was diagnosed Neurofibromatosis type I due to the presence of typical cafe’ au lait macules and pectus carinatum. Whole-exome sequencing identified a synonymous mutation c.6795C>T (p.N2265N) of the NF1 gene which was located at the non-canonical splicing sites. Reverse transcription polymerase chain reaction followed by Sanger sequencing was carried out, and the skipping of exon 45 was observed. Therefore, the pathogenicity of the synonymous mutation c.6795C>T was confirmed. Our finding expanded the spectrum of pathogenic mutations in Neurofibromatosis type I and provided information for genetic counseling.